2011
DOI: 10.1177/2151458511417434
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Reversal of Warfarin-Associated Coagulopathy in Geriatric Patients With Hip Fractures

Abstract: Purpose: Patients with acute hip fractures who are on maintenance warfarin for anticoagulation present a significant challenge and their management remains controversial. The purpose of this study was to assess thromboembolic and systemic complications associated with pharmacological reversal of warfarin-associated coagulopathy in a population of geriatric patients with hip fractures. Methods: This retrospective cohort study identified patients with operative hip fractures on oral warfarin therapy who had an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Our study is the most comprehensive to date to show association between warfarin therapy and delays to the operating room, and therefore should highlight the need to prevent any avoidable preoperative delays in these patients. Early warfarin reversal together with adequate investigation and optimization of these more complex patients could ensure timely, safe surgery [2, 79, 23, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Our study is the most comprehensive to date to show association between warfarin therapy and delays to the operating room, and therefore should highlight the need to prevent any avoidable preoperative delays in these patients. Early warfarin reversal together with adequate investigation and optimization of these more complex patients could ensure timely, safe surgery [2, 79, 23, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Vitale et al 8 conducted a study among 1634 patients presenting to the Columbia Presbyterian Medical Centre (CPMC) between 1997 and 2010, who underwent operative intervention of a hip fracture. Of these, 93 patients (5.7%) were identified as having a pre-operative international normalised ratio (INR) >1.50 and were taking warfarin on admission.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that reversal of warfarin-associated coagulopathy with vitamin K and/or FFP is not associated with a greater rate of post-operative complications in the high-risk geriatric population of patients with hip fractures and was found to be a safe alternative to warfarin cessation alone, which may result in increased delay to surgery. 8 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations